(3ehWC GdEeGe eGdcs - (3eGdc Hf CfS Hf eGdc Hf CHj YGeQ GdCUHMj GdMejQj GdeOfj , CHh YHO Gddg , J (B179 (3g`s
(3ChdgG (B:s
(3hbhJ GdUdGI (B: (3bGd MOKfi jMji Hf jMji GddjKi Yf eGdc Yf GHf TgGH Cf YeQ Hf YHO GdYRjR BNQ GdUdGI jhekG s
(3BNQgG (B:s
(3ef bhdg Udi Gddg Ydjg hSde hCfG GdMGTQ GdPi jMTQ GdfGS Ydi bOei hCfG GdYGbH Je cJGH GdehWC s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI HChdg hba SfI (B1304s
(3QhGjI jMji Hf jMji GddjKis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B186 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B402s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs